Evaluation of paclitaxel-coated balloon angioplasty for the treatment of symptomatic intracranial in-stent restenosis - Xue, Huiyuan; Xi, Junnan; Wu, Xiao Feng; Feng, Songsong; Wang, Juan; Chen, Liwei (Frontiers in Neurology, 2024)
Symptomatic intracranial in-stent restenosis (sISR) presents a significant therapeutic challenge in the management of cerebrovascular diseases. This retrospective study evaluated the efficacy and safety of treating sISR with paclitaxel-coated balloon (PCB) angioplasty in five patients (aged 49-74 years) treated between January 2017 and June 2022. Key evaluation parameters included the assessment of intracranial artery and ISR severity, and the incidence of transient ischemic attacks or strokes. The treatment protocol comprised pre-operative digital subtraction angiography, antiplatelet therapy, and administration of aspirin and clopidogrel, followed by the utilization of the SeQuent Please balloon during the procedure and dual antiplatelet therapy. The procedure boasted a 100% success rate, with a reduction in ISR rate from an average of 72±18.9% pre-operatively to 34±8.22% post-operatively. Long-term follow-ups revealed an absence of restenosis in the majority of patients, demonstrating the procedure's effectiveness and safety. This study highlights paclitaxel-coated balloon angioplasty as a promising treatment option for patients with sISR, particularly those considered high-risk.